ANALISIS FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG SABTU BELANJA DI ALUN-ALUN KARANGANYAR - Nining Putri Astuti, Edi Wibowo & Setyaningsih Sri Utami (Universitas Slamet Riyadi, 2018)
The merchant's income can be affected by various factors. This research is conducted to know the influence of equity, loan capital, and business location on merchant's revenue saturday shopping Karanganyar. The population of this study is all traders saturday shopping as much as 328 traders. The sample used amounted to 77 traders with cluster random sampling sampling method. Data collection techniques used questionnaires and interviews. Methods of data analysis using classic assumption test, multiple linear regression, test t, test F, and coefficient of determination (R2). The result of t analysis shows its equity and loan capital has significant influence to traders' revenue on saturday while business location has no significant effect to merchant's revenue Saturday. Coefficient determination R2 obtained value of adjusted R square of 0,521 this means that the contribution or influence given by the variable of equity, loan capital and business location is 52,1% while 47,9% influenced by other variables outside this study .Keywords: revenue, equity, loan capital, business location